(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the percentage of houses having Motorcycle, Motorcycle accidents and the different pattern of injuries and their frequencies in various age groups caused in Motorcycle accidents during the last one year in district Swat. Study Design: Retrospective study. Place and Duration of Study: This study was conducted at the Department of Community Medicine, Swat Medical College, district Swat from June 2018 to May 2019. Materials and Methods: Out of 65 union councils we have randomly selected 8 union council. The data was collected from the heads of the houses by a pre-tested questionnaire from 536 randomly selected houses in these randomized eight (8) union councils in district Swat, after the informed consent of the heads of the families. Both sex of all ages were included. Results: 204 (38.1 %) out of 536 houses were found to have motorcycles. The percentage of the houses involved in motorcycle accidents were 14.7%. The common injuries found were that of head and neck (31.8%), followed by lower limbs (20.5%) injuries. Conclusion: Motorcycle related morbidities and mortalities remain to be a major public health issue in Swat as well as all over Pakistan. There is an urgent need for an efficacious interventional programs to decline the burden of motorcycle related morbidity and mortalities.